Perancangan Sistem Produksi Yang Optimal untuk Meningkatkan Kapasitas Produksi UMKM Flamboyan Menggunakan Metode Lean Manufaktur - Anom, Adji Saputra; Lahay, Idham Halid; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Flamboyan UMKM is an UMKM engaged in the food sector. They make various types of processed foods, especially processed fish and processed bananas, one of their best-selling products is banana chips with milk and cheese. In the implementation of its production, some waste is still found. To reduce the waste identified in the production process, the application of Lean Manufacturing with the VSM (Value Stream Mapping) method is used to analyze and design the flow of materials and information so that it can identify, analyze and find solutions to make improvements to reduce the waste that occurs. In its implementation, it began with the identification of waste that occurred using interviews and direct observations in the field. The results of waste identification obtained waste at the banana storage work station in the freezer with an average time of 12000 seconds or 200 minutes or 3.33 hours. After the improvements were made, to reduce waste, 1 work station was added so that the banana storage time in the freezer became 3600 seconds or 60 minutes or 1 hour and 2 places were made to increase efficiency.